An emerging taxonomy explaining mentor-teachers' role in student-teachers' practicum: What they do and to what end?. (July 2023) - Carmi, Tal; Tamir, Eran
Abstract: Rich literature discusses teacher mentoring, provides relevant knowledge, and advances the field. However, it lacks consensus about the meaning of teacher mentoring. Oftentimes teacher mentoring studies rely on predetermined concepts or focus on isolated elements, yet seldom contribute to an overarching theory stemming from the nitty-gritty details that make mentoring essential for novice and veteran teachers. Following a field-grounded theory approach and suspending theoretical presuppositions, this study analyses the daily realities of accomplished mentor-teachers, presenting a comprehensive taxonomy of their practices and goals. This taxonomy can serve as a theoretical and analytical tool for future research and for supporting mentors. Highlights: There is no consensus regarding the concept of teacher mentoring in the literature. Many studies prefer focusing on theoretical frameworks instead of the nitty-gritty details of mentoring. Field-grounded approach suspended theoretical presuppositions and led to an elaborate taxonomy of the mentor-teachers' role. The taxonomy includes six mentoring practices and seven contents of mentoring. This taxonomy can serve researchers and practitioners as a theoretical and analytical tool.